Mental health outcomes and help‐seeking behaviours among Egyptian medical students: A cross‐sectional study. Issue 9 (22nd November 2021) - Kamel, Mostafa M.; Westenberg, Jean N.; Suen, Janet; Jang, Kerry L.; Maragha, Tala; Badawy, Adel; El‐Sawi, Hosam; Krausz, Michael
Abstract: Aim: Approximately half of the population in Egypt is under the age of 25. Globally, mental illness represents the highest burden of disease in this age group. Yet in Egypt, there is still no youth‐specific mental health system in place and the vast majority of young people do not have access to any professional mental health support. The objective of this study was to describe the mental health needs of Egyptian youth and the resources they use when seeking help. Methods: An online cross‐sectional survey was distributed among medical students at Tanta University in Egypt. Of the 707 individuals who completed the survey (90.9% response rate), 60.5% were female, 62.0% lived in urban and suburban areas, and the mean age of the sample was 20.5 (±1.8) years old. Results: More than half (54%) of the students reported that they had been affected by mental health problems at some point in their lives. Anxiety and depression were the most common problems. Regarding help‐seeking behaviours, participants mainly searched the web or spoke to peers and relatives; few reported approaching medical professionals. The majority of participants (59.7%) reported being disappointed with the current mental health care system in Egypt. Conclusions: There is a high prevalence of mental challenges among Egyptian youth and the health care system is not adequately prepared to respond to their needs. E‐Mental Health and online interventions seem to be a promising solution that could increase access to mental health services for Egyptian youth.